2017
DOI: 10.1294/jes.28.61
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the potential roles of the <i>Gray</i> and <i>Extension</i> loci in the coat coloration of Thoroughbred racing horses

Abstract: Horses have substantial variation in coat color, and the genetic loci responsible for the coat color variations have been well investigated. It has been believed that some color variations should follow a single-locus Mendelian law. Examples include the Gray locus that causes the gray phenotype and the Extension locus that specifies the chestnut phenotype. We reevaluated the roles of the Gray and Extension loci by using a large number of mating records of Thoroughbred racing horses. We showed that the data ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…For this locus the authors could not find a difference in colour shade between A/a and A/A. Also Sakamoto et al (2017), who studied segregation ratios by means of pedigree analysis, treated the Extension and Agouti loci separately. For the Agouti locus the authors compared the expected number with the observed number of Our data generally confirm these findings, whereas only the combination of the genotypes A/a with E/E resulted in a statistically confirmed distinct cluster.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…For this locus the authors could not find a difference in colour shade between A/a and A/A. Also Sakamoto et al (2017), who studied segregation ratios by means of pedigree analysis, treated the Extension and Agouti loci separately. For the Agouti locus the authors compared the expected number with the observed number of Our data generally confirm these findings, whereas only the combination of the genotypes A/a with E/E resulted in a statistically confirmed distinct cluster.…”
Section: Discussionmentioning
confidence: 97%
“…In this study we aimed to characterize and examine single loci effects (ASIP and MC1R) on coat colour variability in bay and black horses. Although ASIP and MC1R and their interaction have been studied (Rieder et al 2001;Sponenberg 2009;Sakamoto et al 2017), the reasons for bay coat colour variability ranging from light bay to seal brown are not fully resolved. This led Sponenberg (2009) postulate a dosage effect and the existence of multifactorial genetic control.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although a statistically significant association between MC1R and coat color has been found, this was based on a limited number of horses (n = 120) and only three colors were investigated (Rieder et al, 2001). Another statistical analysis of coat colors based on 153,778 horses generated a hypothesis that MC1R genotypes have a direct effect on eumelanin levels, but indicated that other genes are involved in this process (Sakamoto et al, 2017). While the genotype distribution of MC1R has been studied, the distribution of ASIP genotypes in horses with different coat colors remains unclear and how the combination of the two important genes correlate with the coat color has not been studied.…”
Section: Introductionmentioning
confidence: 99%